2014
DOI: 10.1021/jf500975h
|View full text |Cite
|
Sign up to set email alerts
|

Hormones, Polyamines, and Cell Wall Metabolism during Oil Palm Fruit Mesocarp Development and Ripening

Abstract: Oil palm is one of the most productive oil-producing crops and can store up to 90% oil in its fruit mesocarp. Oil palm fruit is a sessile drupe consisting of a fleshy mesocarp from which palm oil is extracted. Biochemical changes in the mesocarp cell walls, polyamines, and hormones at different ripening stages of oil palm fruits were studied, and the relationship between the structural and the biochemical metabolism of oil palm fruits during ripening is discussed. Time-course analysis of the changes in express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 63 publications
0
20
1
Order By: Relevance
“…However, the dissimilar trend of the upregulated expression until 18 WAA prior to suddenly decreased at 20 WAA was observed in coatomer subunit delta‐2 (spot 1284) which involved in vesicle transport and 14‐3‐3 protein (spot 1364) in signalling. In a disagreement with the present results, the previous study has demonstrated the abundance of actin at 15 and 20 WAA while the gene expression level peaked at 12 and 14 WAA and remained high towards ripening coinciding with the cell expansion during lipid accumulation . The increase in actin during ripening corresponding to oil palm and berry development might be related to cell expansion during lipid accumulation due to involvement in several cellular processes such as cell shape determination, cytoplasmic streaming, extension growth and organelle movement .…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…However, the dissimilar trend of the upregulated expression until 18 WAA prior to suddenly decreased at 20 WAA was observed in coatomer subunit delta‐2 (spot 1284) which involved in vesicle transport and 14‐3‐3 protein (spot 1364) in signalling. In a disagreement with the present results, the previous study has demonstrated the abundance of actin at 15 and 20 WAA while the gene expression level peaked at 12 and 14 WAA and remained high towards ripening coinciding with the cell expansion during lipid accumulation . The increase in actin during ripening corresponding to oil palm and berry development might be related to cell expansion during lipid accumulation due to involvement in several cellular processes such as cell shape determination, cytoplasmic streaming, extension growth and organelle movement .…”
Section: Resultscontrasting
confidence: 99%
“…However, the lignin content was triggered by higher lipid production in mesocarp tissues caused by the down‐regulation of the key enzyme in the lignin biosynthetic pathway i.e. caffeoyl CoA 3‐ O ‐methyltransferase (CCOMT) discordance with the upregulated of ROMT from our finding .…”
Section: Resultsmentioning
confidence: 44%
See 2 more Smart Citations
“…That EgACO and EgPG4 share similar expression profiles with various cell wall modifying protein transcripts suggests ethylene may transcriptionally regulate cell wall activities differentially as proposed previously (Ireland et al, 2014). Previous work on cell wall related gene expression during oil palm mesocarp ripening monitored only very few genes (Teh et al, 2014). In contrast, the current work includes a more comprehensive analysis of 56 differentially expressed genes from at least 20 different cell wall related gene families.…”
Section: Discussionmentioning
confidence: 99%